Taking electrons out of bioelectronics: bioprotonic memories, transistors, and enzyme logic. Issue 25 (7th July 2015) - Hemmatian, Zahra; Miyake, Takeo; Deng, Yingxin; Josberger, Erik E.; Keene, Scott; Kautz, Rylan; Zhong, Chao; Jin, Jungho; Rolandi, Marco
<x xml:space="preserve">Abstract</x> We highlight our recent efforts in developing devices that control the flow of H+ and OH− in biological polymers.